An Analysis of the Financial Performance of Credit Cooperatives in Malaysia - Fatin Syazwani Safiyuddin; Norazlina Abd Wahab; Selamah Maamor (Journal of Accounting Research, Organization and Economics, 2021)
Objective– The aim of this study is to assess the financial performance of credit cooperatives in Malaysia. Design/methodology– This study utilizes the unpublished financial data of credit cooperatives from the Malaysian Cooperative Commission. This study picks 9 credit cooperatives which serially listed in 100 best cooperatives from 2010 to 2017. Five basic financial ratios (equity ratio, liquidity ratio, leverage ratio, profitability ratio, and dividend payout ratio) were calculated to measure the financial performance. Results – The result shows that the equity ratio is in the range of 0.61 to 0.9 possibly because credit cooperatives utilize more funding from shareholder equity compared to debt. The result also shows a high dividend pay-out ratio. However, the liquidity ratio is still low and credit cooperatives that score the highest liquidity ratio might be due to the age of establishment. Last but not least, the leverage ratios and profitability ratios of Malaysian credit cooperatives should be improved by increasing the profitability and restructuring debt.  Research limitations/Implication – The availability of the data as there are other credit cooperatives listed in the top 100 cooperatives from 2010 to 2017 but could not be analyzed because important data such as total investment, loans, equity, dividends are not available. Novelty/Originality – The empirical application of ratio analysis to identify the financial performance facilitates a novel investigation of credit cooperatives performance by placing emphasis on the equity, liquidity, leverage, profitability, and dividend payout of credit cooperatives with various degrees of performance.